501 CASEOUS CALCIFICATION OF THE MITRAL ANNULUS AND THE IMPORTANCE OF ITS IDENTIFICATION IN THE CLINICAL PRACTICE: A REPRESENTATIVE CASE. (15th December 2022) - Ciceri, Luca; Springhetti, Paolo; Dotto, Alberto; Maffeis, Caterina; Tafciu, Elvin; Bergamini, Corinna; Rossi, Andrea; Benfari, Giovanni; Luciano Ribichini, Flavio
Abstract: 1. Introduction: Caseous Calcification of the Mitral Annulus (CCMA) is a rare condition characterized by a liquefaction degeneration that usually involves posterior mitral ring and it is considered a variant of mitral annulus calcification. Its prevalence is very low, but it is possible that it is often underdiagnosed or misdiagnosed. This condition is related with increased age, female sex, chronic kidney disease and calcium metabolism disorders. The lesion can be detected using imaging techniques and its management is conservative in most cases. 2. Case Study: A 72-year-old man hospitalized for bilateral pneumonia complicated with ARDS has come to our attention. The patient had a history of stage IV renal failure, type 2 diabetes mellitus and calcific degenerative aortic valve disease. During its stay in the Intensive Care Unit a routine Transthoracic Echocardiogram showed a vegetation suspected for infective endocarditis that involved the posterior mitral leaflet. However, the clinical presentation did not support endocarditis diagnosis as no microorganisms were isolated at multiple blood cultures and other Duke Criteria were negative. Given the limited acoustic viewing of transthoracic echocardiogram it was necessary to perform a Transesophageal Echocardiogram (TEE) for a better characterization of the valve lesion. TEE showed the presence of a round lesion, about 2×2 cm in size, with smooth borders, located over the mitral annulus with extension up to the posterior mitral leaflet and with a partially mobile portion. The lesion had a corpuscular appearance inside with less echogenicity and without evidence of flow. No significant functional alterations of the mitral valve were detected (anterograde transmitral flow Mean Gradient 4-5 mmHg; Mild regurgitation). We therefore concluded for Caseous Calcification of the Mitral Annulus as the most likely diagnosis and decided for a conservative management. A new TEE was performed as a control after one week showing no significant changes on the valve lesion. 3. Conclusions: It is important for echocardiographers to be familiar with CCMA and to know how to distinguish it from other valve lesions such as infective vegetation, abscesses or tumors. An integration with other cardiac imaging techniques, patient past medical history and clinical-laboratory data can help the physician in the correct characterization of valve lesions and subsequent most appropriate therapeutic approach for the patient.